A new species of the genus Mecistoscelis Reuter from Vietnam (Hemiptera: Miridae: Mecistoscelini), with key to Mecistoscelis species - Kim, Junggon; Roca-Cusachs, Marcos; Pham, Hong-Thai; Jung, Sunghoon (Zootaxa, 2018)
A new species, Mecistoscelis lansburyi Kim et Jung sp. nov. is described from Vietnam. Diagnosis, description including genitalia, and biological notes are presented with illustrations and photographs. The photographic image of female genital structure of this tribe is first presented based on M. lansburyi sp. nov. and key to the Mecistoscelis species is provided.